Carbon-based electrode materials, batteries, and electrical devices

By performing multi-segment fitting on the self-discharge curves of carbon-based electrode materials, suitable carbon-based electrode materials were selected, solving the problem of the complexity of self-discharge of carbon-based electrode materials, reducing self-discharge loss, and improving the energy storage efficiency and stability of the battery.

CN118231655BActive Publication Date: 2026-01-06BYD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311261113.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-27
Publication Date
2026-01-06
Estimated Expiration
2043-09-27

AI Technical Summary

Technical Problem

In existing technologies, the self-discharge phenomenon of carbon-based electrode materials is complex and difficult to analyze accurately, leading to excessively rapid consumption of lithium battery energy storage, increased storage costs, and potential side reactions.

Method used

By performing multi-segment fitting on the self-discharge curve of carbon-based electrode materials, using multiple preset functions to obtain the initial voltage, transition voltage, and termination voltage, calculating the voltage difference ratio, suitable carbon-based electrode materials are selected to reduce self-discharge loss.

Benefits of technology

This enabled accurate screening of carbon-based electrode materials, reduced self-discharge loss, and improved the energy storage efficiency and stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118231655B_ABST
    Figure CN118231655B_ABST
Patent Text Reader

Abstract

The application provides a carbon-based electrode material, a battery and a power utilization device, and the carbon-based electrode material meets the following requirements: a self-discharge curve of the carbon-based electrode material is obtained by performing self-discharge curve processing on the carbon-based electrode material, an initial voltage and a terminal voltage of the carbon-based electrode material are obtained according to the self-discharge curve, and a difference between the initial voltage and the terminal voltage is determined as a first voltage difference; a first transition voltage of the carbon-based electrode material is obtained by fitting the self-discharge curve through a plurality of preset functions, and a difference between the initial voltage and the first transition voltage is determined as a second voltage difference; and a ratio of the second voltage difference to the first voltage difference is greater than a preset ratio of 33.3%. The scheme can fully utilize the self-discharge curve characteristics of the material to screen the carbon-based electrode material, can more accurately screen the suitable carbon-based electrode material, and reduces the self-discharge loss of the selected carbon-based electrode material in actual application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrode technology, and more specifically to a carbon-based electrode material, a battery, and an electrical device. Background Technology

[0002] Carbon-based materials are widely used as electrode materials in lithium-ion batteries, sodium-ion batteries, zinc-ion batteries, and capacitors due to their large specific surface area, rich and tunable surface structures (such as layering, edge defects, and pores), and excellent conductivity. The rich and tunable surface structures contribute to the large specific surface area of ​​carbon-based materials, along with functional groups that provide wettability and enhance redox reactions, resulting in high energy density and significantly improved electrochemical performance. Furthermore, as green energy materials, carbon-based materials are made from abundant raw materials, have diverse preparation methods, low pollution, and high recyclability, making them poised to play a significant role in future energy storage applications.

[0003] Meanwhile, complex surface structures can also introduce self-discharge issues into carbon-based materials, affecting the capacity changes of the battery cell during long-term storage. Furthermore, different types of surface structures will have varying effects on the self-discharge of carbon-based materials, further complicating the analysis of self-discharge in these materials.

[0004] For lithium batteries, excessive self-discharge can lead to rapid depletion of battery energy storage, increasing storage costs. In more severe cases (low voltage due to self-discharge), it may induce side reactions on the carbon-based surface (such as SEI film damage and electrolyte decomposition), even resulting in irreversible capacity decay.

[0005] There is a lot of research on self-discharge of batteries (button batteries, pouch batteries, and battery packs), but there is very little research on self-discharge of carbon-based materials. Summary of the Invention

[0006] The purpose of this invention is to provide a carbon-based electrode material, a battery, and an electrical device that can fully utilize the self-discharge curve characteristics of the material to screen carbon-based electrode materials, thereby more accurately selecting suitable carbon-based electrode materials and reducing the self-discharge loss of the selected carbon-based electrode materials in practical applications.

[0007] To achieve the above objectives, a first aspect of the present invention provides a carbon-based electrode material, wherein the carbon-based electrode material satisfies the following requirements: the carbon-based electrode material is subjected to self-discharge curve processing to obtain a self-discharge curve of the carbon-based electrode material; an initial voltage and a termination voltage of the carbon-based electrode material are obtained based on the self-discharge curve; the difference between the initial voltage and the termination voltage is determined as a first voltage difference; the self-discharge curve is fitted using multiple preset functions to obtain a first transition voltage of the carbon-based electrode material; the difference between the initial voltage and the first transition voltage is determined as a second voltage difference; and the ratio of the second voltage difference to the first voltage difference is greater than a preset ratio of 33.3%.

[0008] Optionally, the carbon-based electrode material also meets the following requirements: the self-discharge curve is fitted by a plurality of preset functions to obtain the target coefficient of each of the plurality of preset functions; and the target coefficient of each preset function is within a set range.

[0009] Optionally, the plurality of preset functions include a first function, a second function, and a third function. Fitting the self-discharge curve using the plurality of preset functions includes: performing a regression fitting analysis on the self-discharge curve using the least squares method based on the initial voltage, the termination voltage, the first function, the second function, and the third function to obtain the first transition voltage and the second transition voltage of the carbon-based electrode material, wherein the first transition voltage is the boundary voltage between the first function and the second function, and the second transition voltage is the boundary voltage between the second function and the third function.

[0010] Optionally, the first function is related to the ohmic impedance coefficient; the second function is related to both the first redox coefficient and the second redox coefficient; and the third function is related to the pore volume parameter of the carbon-based material.

[0011] Optionally, the first function can be expressed by the following formula using the initial voltage U0, the first transition voltage U1, and the time t: U1=U0×mexp(-t / R), where the unit of the initial voltage U0 is V, the unit of the first transition voltage U1 is V, and the unit of the time t is s; m is the capacity coefficient, and R is the target coefficient of the first function, with R taking a value between 8*10. 6 ~10*10 6 between.

[0012] Optionally, the second function can be expressed by the following formula using the first transition voltage U1, the second transition voltage U2, and the time t: U2=U1-pLn(t)-q, where the unit of the first transition voltage U1 is V, the unit of the second transition voltage U2 is V, and the unit of the time t is s; Ln(t) is the natural logarithm related to time t, p and q are the target coefficients of the second function, where the value of p is between 0.07 and 0.09, and the value of q is between 1.3 and 1.5.

[0013] Optionally, through the second transition voltage U2 and the termination voltage U t The third function, U, is expressed by the following formula, given time t: t =U2-nt -1 / 2 Wherein, the unit of the second transition voltage U2 is V, and the unit of the termination voltage U... t The unit is V, the unit of time t is s; n is the target coefficient of the third function, and the value of n is between 35 and 42.

[0014] Optionally, when the carbon-based electrode material is the negative electrode material of the battery, the self-discharge curve processing of the carbon-based electrode material includes: preparing the carbon-based electrode material into a coin cell, and collecting data points of the open-circuit voltage of the coin cell at set intervals during the resting time of the coin cell.

[0015] The beneficial effects of this invention through the above technical solution are as follows: the initial voltage, termination voltage, and transition voltage of the carbon-based electrode material can be obtained through its self-discharge curve, and the target carbon-based electrode material can be screened by the voltage ratio of the target voltage range in the entire self-discharge range. This invention fully utilizes the self-discharge curve characteristics of materials to screen carbon-based electrode materials, enabling more accurate selection of suitable materials and reducing self-discharge losses in practical applications.

[0016] A second aspect of the invention also provides a battery made of the carbon-based electrode material described above.

[0017] A third aspect of the present invention also provides an electrical device comprising the battery described above.

[0018] For specific details and benefits of the batteries and power devices provided in the embodiments of the present invention, please refer to the above description applicable to carbon-based electrode materials, which will not be repeated here.

[0019] Other features and advantages of the embodiments of the present invention will be described in detail in the following detailed description section. Attached Figure Description

[0020] The accompanying drawings are provided to further illustrate embodiments of the present invention and form part of the specification. They are used together with the following detailed description to explain the embodiments of the present invention, but do not constitute a limitation thereof. In the drawings:

[0021] Figure 1 This is a schematic diagram illustrating the requirements to be met by a carbon-based electrode material provided in an embodiment of the present invention;

[0022] Figure 2 This is a schematic diagram illustrating additional requirements to be met by a carbon-based electrode material provided in an embodiment of the present invention;

[0023] Figures 3a-3d This is a schematic diagram of the various self-discharge stages calculated from multiple types of carbon-based materials selected in an embodiment of the present invention;

[0024] Figure 4 This is a schematic diagram showing the self-discharge range percentages calculated from various types of carbon-based materials selected in an embodiment of the present invention;

[0025] Figure 5 This is a schematic diagram illustrating the self-discharge characteristic trends of various carbon-based materials selected in an embodiment of the present invention. Detailed Implementation

[0026] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. It should be understood that the specific embodiments described herein are for illustration and explanation only and are not intended to limit the scope of the present invention.

[0027] In a first aspect, the present invention provides a carbon-based electrode material, such as... Figure 1 As shown, carbon-based electrode materials need to meet the requirements of the following steps S110-S130.

[0028] S110, perform self-discharge curve processing on the carbon-based electrode material to obtain the self-discharge curve of the carbon-based electrode material, obtain the initial voltage and termination voltage of the carbon-based electrode material based on the self-discharge curve, and determine the difference between the initial voltage and the termination voltage as the first voltage difference.

[0029] Specifically, the carbon-based electrode material can first be fabricated into a carbon-based electrode, and then the carbon-based electrode can be fabricated into the negative electrode of the battery. The carbon-based electrode material can be graphite, hard carbon, or modified hard carbon materials, or it can be graphene, carbon nanotubes, or other modified carbon-based materials, such as destructively pulverized graphite materials or destructively pulverized graphite materials activated and etched with KOH to create pores. The battery can be a coin cell. More preferably, the coin cell can be a coin cell assembled using an aqueous button cell assembly method.

[0030] The self-discharge curve processing of carbon-based electrode materials may include: collecting data points of the battery's open-circuit voltage at set intervals during a set battery resting period. For example, a resting time method can be used to run the battery prepared in the above steps and record the resting-initial voltage U0 and the resting-termination voltage U0. t The voltage accuracy requirement can be 0–15 mV. Simultaneously, the voltage decay change per unit time is measured to obtain the battery's self-discharge voltage dataset. Optionally, the time interval can be set to 24–72 h, and / or the interval to be set to 0.3–2 s (i.e., data points are collected every 0.3–2 s). This acquisition method has the advantage of not requiring large-scale data accumulation and not needing to adjust the open-circuit potential analysis for the material based on the SOC status.

[0031] Carbon-based electrodes can be prepared using various known methods. For example, an electrode slurry can be prepared by mixing carbon-based material, KB, and PTFE in a ratio of 85:5:10 (other ratios can also be chosen) with an appropriate amount of anhydrous ethanol. The electrode slurry is then rolled into a film, cut into round discs with a diameter of 5-15 mm using a die-cutting machine, dried, and then pressed onto a current collector using a die-pressing machine. For example, the current collector can be nickel foam.

[0032] For the fabrication of coin cells, various known methods can be employed. For example, aqueous symmetrical coin cell assembly can be used to reduce the influence of other materials. Specifically, the prepared carbon-based electrodes can be baked at 100-120℃ for 6-8 hours, and two electrode sheets with similar active material masses can be assembled into a coin cell and allowed to stand for 24-72 hours. The electrolyte for the coin cell can be a 6 mol / L KOH aqueous solution. Based on the active material mass and operating voltage range of the battery, the prepared electrodes are assembled into a three-electrode configuration to measure the voltage coefficient (CV), confirming the main energy storage type of the carbon-based material and the potentials of the redox reactions present.

[0033] Before the initial resting period, the battery can undergo 5-10 charge-discharge cycles at a rate of 0.5-1.0C to fully immerse the electrode plates. Record the capacity data from the last cycle. For example, after the 5th cycle, perform constant current and constant voltage charging at 0.5-1.0C, with a cutoff voltage of 1.0-1.5V for 30-60 minutes. After completing these steps, begin measuring self-discharge using the resting time method. Record the cutoff voltage after the test and perform 3-5 charge-discharge cycles at 0.5-1.0C, recording the battery capacity. This process effectively eliminates the effects of insufficient initial immersion and side reactions, making subsequent test data more reliable.

[0034] Step S120: Fit the self-discharge curve using multiple preset functions to obtain the first transition voltage of the carbon-based electrode material, and determine the difference between the initial voltage and the first transition voltage as the second voltage difference.

[0035] In fitting open-circuit voltage, most current fitting methods increase the order of mathematical functions and employ two-stage interval analysis. While these methods achieve a certain degree of fit, they do not fully capture the actual reaction level of the material. However, the inventors of this application discovered during the implementation of the embodiments of this invention that the curve of open-circuit voltage, as a parameter that clearly describes self-discharge phenomena, is affected by the characteristics of the material.

[0036] Specifically, the initial voltage U0 can be used as the starting point and the ending voltage U t With the endpoint being the settling time method, the data points collected are plotted as Vt curves, and the self-discharge curve of the carbon-based electrode is fitted in a multi-segment manner.

[0037] Here, the transition voltage is the boundary voltage between two adjacent preset functions among multiple preset functions. That is, it can be understood that a certain transition voltage is the end point of the previous preset function and the starting point of the next preset function. Therefore, the number of transition voltages is one less than the number of preset functions.

[0038] Preferably, this multi-segment fitting is a three-segment fitting. In this case, the multiple functions may include a first function, a second function, and a third function, and the multiple transition voltages may include a first transition voltage and a second transition voltage. Therefore, in this embodiment, the entire fitting curve is divided into intervals using the first function, the second function, and the third function. Correspondingly, the self-discharge curve can be divided into a first interval, a second interval, and a third interval in sequence, thereby further analyzing the self-discharge factors of carbon-based materials. The first transition voltage is the boundary voltage between the first function and the second function, and the second transition voltage is the boundary voltage between the second function and the third function. The first transition voltage and the second transition voltage can then be obtained by the following method: based on the initial voltage, the termination voltage, the first function, the second function, and the third function, a regression fitting analysis of the self-discharge curve is performed using the least squares method to obtain the first transition voltage and the second transition voltage.

[0039] Based on the above method, the entire interval is fitted to identify each transition voltage node. For example, the voltage corresponding to the endpoint of the first function is identified as the first transition voltage U1, the voltage corresponding to the endpoint of the second function is identified as the second transition voltage U2, and the voltage corresponding to the endpoint of the third function is identified as the termination voltage U. t (This can also be called the third transition voltage). Specifically, the least squares method can be used, based on the initial voltage U0 and the termination voltage U... t Regression fitting analysis was performed on the self-discharge voltage dataset using the first, second, and third functions to obtain the correlation coefficient r. 2 The first transition voltage U1 and the second transition voltage U2 are greater than the set values. The least squares method is used for fitting, which ensures reliable data and high fitting degree. Improving the accuracy of piecewise curve fitting analysis enhances this. Compared to control experiments that merely describe the self-discharge performance of materials through the decrease in potential per unit time, the present invention can more accurately analyze the self-discharge of carbon-based electrode materials, with better fitting results and higher accuracy.

[0040] With multiple preset functions, including a first function, a second function, and a third function, the analysis and fitting of the self-discharge curve is no longer attributed to one or two single causes, but is precisely divided into three stages, with each stage corresponding to a different self-discharge reaction range of the carbon-based material. This invention employs a multi-segment fitting method, observing curve characteristics and confirming the inflection points (i.e., transition voltages) of specific stages, reflecting the different structures and main energy storage characteristics of the carbon-based material corresponding to each stage, enabling targeted analysis.

[0041] In one embodiment, Matlab fitting software can be used to perform regression fitting analysis, making the fitting process simple and time-saving. In another embodiment, the curve fitting can be iterated until the correlation coefficient r is reached by self-calibrating the parameters in the first, second, and third functions. 2 It reaches 0.98 or above.

[0042] S130, the ratio of the second voltage difference to the first voltage difference is greater than a preset ratio.

[0043] Specifically, this invention analyzes and extracts features from the self-discharge curves of carbon-based electrode materials to obtain the voltage ranges of multiple curve segments and their proportions in the voltage range of the entire self-discharge curve, thereby analyzing and identifying the characteristics of carbon-based electrode materials and identifying the main influencing factors affecting the self-discharge of carbon-based electrode materials.

[0044] In one embodiment, the difference between the initial voltage and the termination voltage is defined as the first voltage difference, and the difference between the initial voltage and the first transition voltage is defined as the second voltage difference. The ratio of the second voltage difference to the first voltage difference should be greater than a preset ratio.

[0045] In one embodiment, the preset ratio can be between 25% and 40%. Generally, the first interval corresponding to the first function is the ohmic impedance stage, which is related to the ohmic impedance coefficient. In this stage, the contact resistance between the material and the electrolyte surface is mainly determined by the overall structure of the material, such as particle size, specific surface area, and porosity; different materials in the same system show little difference. The second interval corresponding to the second function is the redox stage, which corresponds to the material's reaction, mainly involving surface defects and impurities. The third interval corresponding to the third function is the diffusion stage, which is related to the material's mass transfer resistance and is related to its planar or lamellar structure. Therefore, a larger proportion of the first interval indicates that self-discharge mainly occurs in the ohmic impedance stage, while self-discharge is less in the redox or diffusion stages, making it more suitable as a material for carbon-based electrodes.

[0046] For example, the preset ratio can be set to 1 / 3. In this case, if the ratio of the second voltage difference to the first voltage difference is greater than 33.3%, it means that this voltage range is the target range to be selected. It can be considered that the ohmic impedance is the main influencing factor on the self-discharge reaction of the carbon-based material, and it also means that this material is the carbon-based electrode material to be selected in this invention. However, if the ratio of the second voltage difference to the first voltage difference is less than the preset ratio, for example, less than 33.3%, it means that there are other voltage ranges (redox stage or diffusion stage) that have a greater influence on the self-discharge reaction of the carbon-based material, and this material is difficult to use as a material suitable for carbon-based electrodes.

[0047] The beneficial effects of this invention through the above technical solution are as follows: the initial voltage, termination voltage, and transition voltage of the carbon-based electrode material can be obtained through its self-discharge curve, and the target carbon-based electrode material can be screened by the voltage ratio of the target voltage range in the entire self-discharge range. This invention fully utilizes the self-discharge curve characteristics of materials to screen carbon-based electrode materials, enabling more accurate selection of suitable materials and reducing self-discharge losses in practical applications.

[0048] In one embodiment, the carbon-based electrode material of the present invention also needs to meet the requirements of the following steps S210-S220.

[0049] S210 uses multiple preset functions to fit the self-discharge curve in order to obtain the target coefficient of each preset function.

[0050] S220, the target coefficient of each preset function is within the set range.

[0051] Specifically, the first function, the second function, and the third function mentioned above may include the following:

[0052] (1) The first function can be related to the ohmic impedance coefficient, specifically relating to the contact resistance between the carbon-based electrode material and the electrolyte surface. In one embodiment, the first function can be:

[0053] U1 = U0 × mexp(-t / R),

[0054] Where U1 is the first transition voltage (in V), U0 is the initial voltage (in V), and the difference between U0 and U1 is a parameter related to ohmic impedance, which can be denoted as U0. dc .

[0055] m is the coin capacitance coefficient, which is the rated specific capacitance of the carbon-based electrode material relative to its remaining capacity and rated capacity. It can be used to characterize parameters related to coin capacitance and is obtained through actual measurement.

[0056] t represents time (in seconds) and can be used to characterize the duration of the interval.

[0057] R is the target coefficient of the first function, i.e., the ohmic impedance coefficient related to the basic physical properties of the carbon-based electrode material, and its range can be 8*10. 6 ~10*10 6 Between. Preferably, the value is between 9*10. 6 ~10*10 6Between. Generally speaking, the larger this value is, the smaller the first interval is, and the smaller the contact resistance between the material and the electrolyte surface. This indicates that the material surface structure is easier to wet, and also means that there are fewer microporous structures and defects, and more planes.

[0058] (2) The second function can be related to the redox coefficient, specifically relating to the reaction behavior of carbon-based materials. In one embodiment, the second function can be:

[0059] U2 = U1 + pLn(t) - q,

[0060] Where U1 is the first transition voltage (in V), U2 is the second transition voltage (in V), and the difference between U1 and U2 is a parameter related to redox reactions, which can be denoted as U0. ox .

[0061] Ln(t) is the natural logarithm function related to time t.

[0062] p and q are the target coefficients of the second function, namely, the first redox coefficient and the second redox coefficient, respectively. Additionally, p and q are also related to the peak area of ​​the CV test curve and the material defect content. Generally, the larger the values ​​of these two values, the higher the overall self-discharge rate of the material, which has an adverse effect on its self-discharge. However, the applicant discovered during the implementation of this invention that trace redox reactions within a specified range can have a certain positive impact on the self-discharge effect. For example, when the value of p is between 0.07 and 0.09 and the value of q is between 1.3 and 1.5, the slow redox reaction weakens the influence of ohmic impedance and diffusion on self-discharge, thereby reducing the self-discharge of the carbon-based electrode material. Preferably, the value of p is between 0.075 and 0.082 and the value of q is between 1.30 and 1.32.

[0063] (3) The third function can be related to the structural parameters of the carbon-based material, specifically the resistance during the mass transfer stage of the carbon-based material. In one embodiment, the third function can be:

[0064] U t =U2-nt -1 / 2 ,

[0065] Where, U2 is the second transition voltage (in V), U t The termination voltage (in V) is U2 and U t The difference between them is a parameter associated with the diffusion impedance, which can be denoted as U. df .

[0066] n is the target coefficient of the third function, which is a parameter related to the structure (e.g., pore volume) of carbon-based materials. Generally, a larger value indicates more planar and microporous structures, relatively larger defects, fewer oxide functional groups and surface active sites, and may be more susceptible to slow diffusion. This is because ions, influenced by the concentration gradient from planar and microporous structures, slowly diffuse towards lower concentration regions, leading to a decrease in charge and manifesting as self-discharge. Therefore, a larger value represents a larger third range, a higher diffusion resistance, and a more easily diffused surface structure. Thus, its range needs to be controlled between 35 and 42.

[0067] Using the three functions mentioned above for fitting can reflect the characteristics of the material, ensuring that the fitting equation is not a single univariate or multivariate equation or a trigonometric function tan(x), but rather a function related to the material's inherent characteristics. Furthermore, the fitting stage is confirmed to consist of three segments with a fixed order, resulting in fitted data that more closely approximates the true values. This allows for an accurate correspondence between the structure and properties of carbon-based materials, and a precise description of their self-discharge behavior. Moreover, it can be combined with the material's specific surface area and electrochemical performance to more closely approximate the material's actual performance.

[0068] The beneficial effects of this invention through the above technical solution are as follows: Target coefficients of multiple preset functions fitted to the self-discharge curve of the carbon-based electrode material can be obtained, and then target carbon-based electrode materials can be screened based on the range of the target coefficients. This invention fully utilizes the self-discharge curve characteristics of materials to screen carbon-based electrode materials, enabling more accurate selection of suitable materials and reducing self-discharge losses in practical applications.

[0069] A second aspect of the invention also discloses a battery made of the carbon-based electrode material described above.

[0070] A third aspect of the present invention also discloses an electrical device comprising the battery described above.

[0071] For specific details and benefits of the batteries and power devices provided in the embodiments of the present invention, please refer to the above description applicable to carbon-based electrode materials, which will not be repeated here.

[0072] The embodiments of the present invention will be further described in detail below through several specific experiments as examples and in conjunction with the accompanying drawings. The results are as follows: Figures 3a-3c , Figure 4 as well as Figure 5 As shown.

[0073] Example 1: This example selects a type A carbon-based material. Specifically, the material is fabricated into an electrode sheet, assembled using an aqueous coin electrode, tested, and the test data is collected, followed by multi-segment analysis and fitting. The target coefficients R, p, q, and n of several preset functions of the type A material are obtained. The initial voltage U of the type A material is also obtained. 1-0 Termination voltage U 1-t First transition voltage U 1-1 '、Second Transition Voltage U 1-2 The results are summarized in Tables 1 and 2, respectively, and the percentage of each interval is calculated. Specifically, the initial voltage U is used... 1-0 With the first transition voltage U 1-1 'Determine the first interval U' dc Using the first switching voltage U 1-1 'With the second transition voltage U 1-2 'Determine the second interval U' ox Using the second switching voltage U 1-2 'With termination voltage U 1-t The third interval U is determined df .

[0074] Comparative Example 1 uses a type B carbon-based material. Specifically, this material is fabricated into an electrode sheet, assembled using an aqueous coin electrode, tested, and the test data is collected, along with multi-segment analysis and fitting. The target coefficients R, p, q, and n of several preset functions for the type B material are obtained. The initial voltage U of the type B material is also obtained. 2-0 Termination voltage U 2-t First transition voltage U 2-1 '、Second Transition Voltage U 2-2 The results are summarized in Tables 1 and 2, respectively, and the percentage of each interval is calculated. The remaining parameters can be obtained by referring to Example 1.

[0075] Comparative Example 2 uses a type C carbon-based material. Specifically, this material is fabricated into an electrode sheet, assembled using an aqueous coin electrode, tested, and the test data is collected, followed by multi-segment analysis and fitting. The target coefficients R, p, q, and n of several preset functions for the type C material are obtained. The initial voltage U of the type C material is also obtained. 3-0 Termination voltage U 3-t First transition voltage U 3-1 '、Second Transition Voltage U 3-2 The results are summarized in Tables 1 and 2, respectively, and the percentage of each interval is calculated. The remaining parameters can be obtained by referring to Example 1.

[0076] Example 2 uses a type D carbon-based material. Specifically, the material is fabricated into an electrode sheet, assembled using an aqueous coin electrode, tested, and the test data is collected, followed by multi-segment analysis and fitting. The target coefficients R, p, q, and n of several preset functions for the type D material are obtained. The initial voltage, termination voltage, first transition voltage, and second transition voltage of the type D material are obtained and summarized in Tables 1 and 2, respectively, and the intervals and their proportions are calculated. The remaining parameters can be obtained as in Example 1.

[0077] Comparative Example 3 uses a carbon-based material of type E. Specifically, this material is fabricated into an electrode sheet, assembled using an aqueous coin electrode, tested, and the test data is collected, along with multi-segment analysis and fitting. The target coefficients R, p, q, and n of several preset functions for the type E material are obtained. The initial voltage, termination voltage, first transition voltage, and second transition voltage of the type E material are obtained and summarized in Tables 1 and 2, respectively, and the intervals and their proportions are calculated. The remaining parameters can be obtained by referring to Example 1.

[0078] CV test

[0079] The CV curves were measured using a three-electrode cyclic voltammetry method. The instrument used was a CHI 660C electrochemical workstation with Ag / AgCl as the reference electrode. The electrochemical window was 0–1 V, the scan rate was 0.02 V / s, and the sampling interval was 0.005 mV.

[0080] Specifically, the resting time method can be used to measure the voltage decay change per unit time. Before the resting period, the battery undergoes 5 cycles of charge-discharge testing at a charge-discharge rate of 0.5C to fully immerse the electrode plates, and the capacity data of the 5th cycle is recorded. After the 5th cycle, constant current and constant voltage charging is performed at 0.5C, with a cutoff voltage of 1.0V and a time of 30 minutes. After completing the above steps, the self-discharge is measured using the resting time method. Data points are collected every 0.5 seconds, and the test time is 48 hours. After the test is completed, the cutoff voltage is recorded, and the battery undergoes 3 cycles of charge-discharge testing at 0.5C, recording the battery capacity. The transition voltage, voltage range, and proportion of each range for various materials are shown in Table 1. As can be seen from Table 1, Class A and Class D materials have the highest capacity retention rates. The capacity retention rate can characterize the self-discharge loss of batteries made from the corresponding materials and can be measured by the cutoff voltage U. t The ratio to the initial voltage U0 was calculated. Therefore, it can be seen from Table 1 that the self-discharge loss of the type A material in Example 1 and the type D material in Example 2 is smaller.

[0081] Table 1

[0082]

[0083] Table 1 also shows the U values ​​of materials in categories B, C, and E. ox The effect is more pronounced than in types A and D. Furthermore, comparing the capacity retention before and after capacity changes also shows that the capacity change in type E materials is more significant compared to types B and C, due to losses caused by the redox phase. In contrast, the main losses in types A and D materials originate from diffusion resistance. This is because the energy storage in these materials largely relies on interfacial adsorption (due to electrostatic forces) of the double layer; the outer layer has weaker adsorption forces and is located in the electrolyte, making it easy for adsorbed charges to diffuse. Additionally, as... Figure 5 As shown, the curves for materials A and D are flat, without obvious redox peaks. In contrast, materials B, C, and E exhibit a pair of redox peaks within the electrochemical window, while the redox peaks of material E are more pronounced.

[0084] Self-discharge multi-segment fitting

[0085] The multi-segment characteristic curve fitting analysis method of this invention can partition the self-discharge of carbon-based materials, and accurately describe the loss of open-circuit potential by combining the material characteristics. Table 2 summarizes the multi-segment self-discharge fitting data of the materials in the above embodiments and comparative examples.

[0086] Table 2

[0087] Category A materials Category B materials Class C materials Category D materials Class E materials R <![CDATA[9.6012*10 6 ]]> <![CDATA[8.12*10 6 ]]> <![CDATA[8.09*10 6 ]]> <![CDATA[9*10 6 ]]> <![CDATA[8.4*10 6 ]]> p 0.081 0.0879 0.0859 0.077 0.083 q 1.31 1.33 1.45 1.31 1.38 n 41.01 46.9 32.4 36.8 54.5

[0088] As can be seen from the above embodiments and comparative examples, the self-discharge curves of these five types of materials are not entirely consistent. They all exhibit a decreasing voltage trend, with the potential tending to level off after 22 hours. However, the decreasing trend and slope differ among the various materials, indicating that the main factors influencing self-discharge are different for these five types of materials, and are also related to the structure and properties of the materials themselves.

[0089] Specifically, as shown in Table 1, the first transition voltage U1 of material A is 0.88V, and the second transition voltage U2 is 0.88V. Combining this with the target coefficients of the preset functions in Table 2, the corresponding function for material A is:

[0090] U1 = mexp(-t / 9.6012*10 6 ),

[0091] U2 = 0.88 + 0.081Ln(t) - 1.31,

[0092] U t =0.88-41.01t -1 / 2 .

[0093] The first transition voltage U1 of the B-type material is 0.95V, and the second transition voltage U2 is 0.67V. The corresponding function is:

[0094] U1 = mgp(-t / 8.12*10) 6 ),

[0095] U2 = 0.95 + 0.0879Ln(t) - 1.33,

[0096] U t =0.67-46.9t -1 / 2 .

[0097] The first transition voltage U1 of the C-type material is 0.96V, and the second transition voltage U2 is 0.56V. The corresponding function is:

[0098] U1 = mexp(-t / 8.09*10 6 ),

[0099] U2 = 0.96 + 0.0859Ln(t) - 1.45,

[0100] U t =0.56-32.4t -1 / 2 .

[0101] The first transition voltage U1 of the type D material is 0.85V, and the second transition voltage U2 is 0.8V. The corresponding function is:

[0102] U1 = mexp(-t / 9*10) 6 ),

[0103] U2 = 0.85 + 0.077Ln(t) - 1.31,

[0104] U t =0.8-36.8t -1 / 2 .

[0105] The first transition voltage U1 of the E-type material is 0.76V, and the second transition voltage U2 is 0.45V. The corresponding function is:

[0106] U1 = mexp(-t / 8.4*10 6 ),

[0107] U2 = 0.76 + 0.083Ln(t) - 1.38,

[0108] U t =0.45-54.5t -1 / 2 .

[0109] In addition, such as Figure 3a and Figure 4As shown, the initial decline of Class A materials was rapid, but it quickly leveled off later, mainly manifested as U dc and U df The values ​​are relatively large (large proportion), accounting for 46.15% and 53.85% respectively, while U is not present. ox Interval phase. It can be seen that the target interval U... dc The proportion is 46.15%, which is greater than the preset proportion of 33.3%, and the target coefficients R, p, q, and n of its preset function are all within the set range. Therefore, this material can be used as a carbon-based electrode material. The main reason is related to the structure and energy storage method of Class A materials. Specifically, Class A materials may have a layered structure, and in the energy storage process, they mainly rely on double-layer adsorption and a small amount of insertion and extraction reactions. In the open circuit case, the decrease in potential is only due to the decrease in interfacial adsorption force and its own impedance, so no large reaction occurs.

[0110] Materials in categories B and C are different, as shown in Table 1. Figures 3b-3c as well as Figure 4 It can be seen that the U of materials in categories B and C... df and U ox Because of their relatively large proportion, the open-circuit voltage will show a transition trend earlier (i.e., the transition node voltages U1 and U2 are relatively large), which is also related to... Figure 5 The peak areas on the surface of the CV curves are consistent. Among them, the U of the B-type material... ox The interval accounted for 56%, U df The interval accounted for 34%, and since both of them accounted for a relatively high percentage, it can be considered that U... ox The corresponding factors (redox resistance) and U df The corresponding factor (diffusion impedance) is an influencing factor on the self-discharge reaction of Class B materials. The target range U... dc The proportion is 10%, which is less than the preset proportion of 33.3%, and the target coefficients R, p, q, and n of its preset function are all outside the set range. Therefore, this material is not suitable as a material for carbon-based electrodes.

[0111] Meanwhile, U of Class C materials ox The interval accounted for 72.73%, U df The interval accounted for 20%, with only U... ox If the interval percentage is greater than the preset percentage of 33.3%, then U can be considered... ox The corresponding factor (redox resistance) is an influencing factor on the self-discharge reaction of Class C materials. The target range U... dc The proportion of this material is only 7.27%, which is less than the preset proportion of 33.3%, and the target coefficients R, p, q, and n of its preset function are all outside the set range. Therefore, this material is also unsuitable as a material for carbon-based electrodes.

[0112] This is because, compared to type A materials, both type B and type C materials have more complex surface structures (such as the simultaneous presence of layers and pores) and a smaller number of surface active sites (heterogeneous elements and functional groups). This leads to multifaceted effects on potential loss in the open-circuit condition. Furthermore, compared to type B materials, type C materials are more susceptible to diffusion resistance and redox reactions caused by their porous structure, which is reflected in the transition node voltages (U1 and U2) and the region proportion (U... df and U ox This is reflected in all of them.

[0113] Therefore, for Class B materials, redox resistance and diffusion resistance have a significant impact on electrode self-discharge, making these materials unsuitable for use as carbon-based electrodes. Similarly, for Class C materials, it can be seen that redox resistance and diffusion resistance have a significant impact on electrode self-discharge, with redox resistance having a more pronounced effect; therefore, these materials are also unsuitable for use as carbon-based electrodes.

[0114] For Class D and Class E materials, see Table 1. Figure 3d as well as Figure 4 It can be seen that the target range U for type D materials dc The proportion is 51.72%, which is greater than the preset proportion of 33.3%. Simultaneously, the target coefficients R, p, q, and n of its preset function are all within the set range. Therefore, type D materials can be used as carbon-based electrode materials. The target range U for type E materials... dc The proportion of E-type materials is 27.27%, which is less than the preset proportion of 33.3%. At the same time, the target coefficients R, p, q, and n of the preset function are not within the set range. Therefore, E-type materials are not suitable as materials for carbon-based electrodes.

[0115] In summary, the solutions of the embodiments of the present invention can accurately analyze the self-discharge of carbon-based electrode materials and identify the main influencing factors affecting the self-discharge of carbon-based materials, which is of great significance for screening better carbon-based materials.

[0116] It should also be noted that the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus. Unless otherwise specified, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes that element.

[0117] The above are merely embodiments of this application and are not intended to limit the scope of this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of the claims of this application.

Claims

1. A carbon-based electrode material, characterized in that, The carbon-based electrode material meets the following requirements: The carbon-based electrode material is subjected to self-discharge curve processing to obtain a self-discharge curve of the carbon-based electrode material, the initial voltage and the terminal voltage of the carbon-based electrode material are obtained according to the self-discharge curve, and a difference between the initial voltage and the terminal voltage is determined as a first voltage difference; The self-discharge curve is fitted by a plurality of preset functions to obtain a first transition voltage of the carbon-based electrode material, and a difference between the initial voltage and the first transition voltage is determined as a second voltage difference, wherein the self-discharge curve is fitted in three sections, the plurality of preset functions include a first function, a second function, and a third function, the fitted curve of the self-discharge curve is divided into a first interval, a second interval, and a third interval in sequence by the first function, the second function, and the third function, wherein the first transition voltage is a demarcation voltage between the first function and the second function, and the first interval corresponding to the first function is an ohmic impedance stage related to an ohmic impedance coefficient; and The ratio of the second voltage difference to the first voltage difference is greater than a preset ratio of 33.3%.

2. The carbon-based electrode material of claim 1, wherein, The carbon-based electrode material also meets the following requirements: The self-discharge curve is fitted by a plurality of the preset functions to obtain a target coefficient of each preset function in the plurality of preset functions; And The target coefficient of each preset function is within a set interval.

3. The carbon-based electrode material of claim 1, wherein, The fitting of the self-discharge curve by a plurality of preset functions includes: According to the initial voltage, the terminal voltage, the first function, the second function, and the third function, a least squares method is used to regressively fit and analyze the self-discharge curve to obtain a first transition voltage and a second transition voltage of the carbon-based electrode material, wherein the second transition voltage is a demarcation voltage between the second function and the third function.

4. The carbon-based electrode material of claim 3, wherein: The second function is related to both a first redox coefficient and a second redox coefficient; and The third function is related to a structural parameter of the carbon-based material.

5. The carbon-based electrode material of claim 3, wherein, by an initial voltage U 0, first transition voltage U 1, time t The first function is represented by the following equation: , wherein the initial voltage U 0 is in V, the first transition voltage U 1 is in V, the time t is in s; m is a capacity coefficient, R is a target coefficient of the first function, R takes a value between 8*10 6 and 10*10 6 .

6. The carbon-based electrode material of claim 3, wherein, by a first transition voltage U 1. a second transition voltage U 2. time t The second function is represented by the following equation: , wherein the first transition voltage U 1 is in V, the second transition voltage U 2 is in V, the time t t is in s; Ln(t) is a natural logarithm related to time, t is a natural logarithm related to time, p and q is a target coefficient of the second function, p has a value between 0.07 and 0.09, q has a value between 1.3 and 1.

5.

7. The carbon-based electrode material of claim 3, wherein, by a second transition voltage U 2. a termination voltage U t , time t The third function is represented by the following equation: , wherein the second transition voltage U 2 in V, the end voltage U t in V, the time t in s; n target coefficients of the third function, n the value of the third function is between 35 and 42.

8. The carbon-based electrode material according to any one of claims 1-7, wherein, In the case where the carbon-based electrode material is a negative electrode material of a battery, the self-discharge curve processing of the carbon-based electrode material includes preparing the carbon-based electrode material into a button cell, and collecting data points of an open-circuit voltage of the button cell at a set interval during a process in which the button cell is left to stand for a set time.

9. A battery, characterized by The battery is made of the carbon-based electrode material of any one of claims 1-8.

10. An electrical device, characterized by The electric device includes the battery of claim 9.

Citation Information

Patent Citations

  • Lithium ion battery self-discharge rate test method, device and system

    CN113064086A

  • Battery self-discharge detection method and system

    CN116626518A